Enantiodivergent routes to (+) and (-)-novioses from (-)-pantolactone - Rajesh, B. M.; Shinde, Madhuri V.; Kannan, M.; Srinivas, Gujjary; Iqbal, Javed; Reddy, D. Srinivasa (RSC Advances, 2013)
Noviose, a rare sugar moiety present in many biologically interesting molecules such as novobiocin and tiacumicin was obtained through formal synthesis in (+)- and (-)-forms starting from commercially available (-)-pantolactone in an enantiodivergent manner.